Strategi Pemberdayaan Soft Skills Penyandang Disabilitas Di Deaf Caede dan Car Wash Cinere Depok Jawa Barat - Septiani Rachmawati; Muhtadi Muhtadi (Program Studi Pengembangan Masyarakat Islam, 2020)
The perception of persons with disabilities as people who cannot do work like non-disabled people makes it difficult for them to find work. With existing deficiencies, people with disabilities are considered to be an obstacle to work and it is difficult to build communication with people with hearing disabilities. Persons with disabilities need a place to accommodate them to get education and training, always given motivation, good communication, advice and infrastructure that supports the situation of persons with disabilities. This study aims to determine (1) the strategy carried out at Deaf Café and Car Wash Fingertalk Cinere, (2) the results of the empowerment carried out, (3) the supporting and inhibiting factors in the implementation of empowerment. This research method uses a qualitative approach using data from observations, interviews, and documentation. The results showed that the empowerment provided has made changes for people with disabilities to become em powered with their own skills, independence, and self-confidence.